Electoral manipulation in March 30, 2014 Turkish local elections. (2nd January 2016) - Aygül, Cenk
ABSTRACT: This article examines the effects of law no 6360 legislated by the Adalet ve Kalkınma Partisi (AKP) before March 2014 local elections in Turkey. The law created 14 new metropolitan municipalities and greatly expanded 14 existing ones. It manipulated the elections first by adding all non-urban districts that were within the administrative borders, and second by dissolving all villages and towns by merging them with metropolitan municipalities. Analyzing the mayoral and councilor competitions, this article models how the elections would have ended had they been held within the pre-6360 borders, and concludes that election results were significantly altered because of distorted representation introduced by the law. Law no 6360 not only created advantages for AKP, but more importantly, it significantly weakened the main opponent Cumhuriyet Halk Partisi .